Procamallanus (Spirocamallanus) spp. (Nematoda: Camallanidae) from fishes of the Okavango River, Botswana, including P. (S.) serranochromis n. sp. parasitic in Serranochromis spp. (Cichlidae) - Moravec, František; Van As, Liesl L (Systematic parasitology, 2015)
Three species of Procamallanus (Spirocamallanus) Baylis, 1923 (Camallanidae) (Nematoda: Camallanidae) were found in the digestive tract of freshwater fishes from the Okavango River, Botswana, i.e. P. (S.) daleneae (Boomker, 1993) from Synodontis vanderwaali Skelton & White (Mochokidae), P. (S.) spiralis Baylis, 1923 from Clarias stappersi Boulenger, C. theodorae Weber (both Clariidae) and Hepsetus odoe (Bloch) (Hepsetidae), and P. (S.) serranochromis n. sp. from Serranochromis macrocephalus (Boulenger) (type-host), S. angusticeps (Boulenger) and S. robustus (Günther) (all Cichlidae). All findings of the two previously known species represent new host records. The specimens were studied using both light and scanning electron microscopy. Spirocamallanus mazabukae Yeh, 1957 is considered a junior synonym of P. (S.) spiralis. A key to the species of Procamallanus (Spirocamallanus) parasitising fishes of continental Africa is provided.
Keywords: Nematoda; hlístice; Animals; mužské pohlaví; Microscopy, Electron, Scanning; Fishes; ženské pohlaví; mikroskopie elektronová rastrovací; zvířata; ryby; Female; řeky; Rivers; Botswana; Cichlids; Male; cichlidy